Seven tips for developing and maintaining a high performance sports medicine team - Gabbett, T. J.; Kearney, S.; Bisson, L. J.; Collins, J.; Sikka, R.; Winder, N.; Sedgwick, C.; Hollis, E.; Bettle, J. M. (British Journal of Sports Medicine, 2018)
In 1989, Stephen Covey published his highly acclaimed book `The 7 Habits of Highly Effective People`.1 This book, with sales exceeding 25 million copies, describes how individuals contribute to successful organisations, in part by fostering interdependence among staff. The multidisciplinary and interdependent nature of high-performance sporting teams have been highlighted in BJSM editorials. Central in these commentaries has been the importance of collective decision-making and shared responsibilities. With sports medicine teams growing rapidly, sport has become somewhat of an `arms race`, with team owners often convinced that the secret to developing a winning franchise lies in the quality of the backroom staff. When assembling a sports medicine team to support the coaches and athletes, what should owners be looking for? What are the characteristics of a highly effective sports medicine team? Here, we provide a perspective from 12 different high-performance organisations based in four countries.